Illegal Oil Bunkering in the Niger Delta Region of Nigeria: A Challenge to Nigeria’s Development - Bodo, Tombari; Gimah, Batombari Gbidum; Seomoni, Kemetonye Joy (European Scientific Journal, ESJ, 2020)
Illegal oil bunkering is a regular activity in the Niger Delta region in Nigeria. Despite the huge financial cost on the part of the government and the multinational oil companies, the perpetrators of this business continue to expand their operations in the creeks. Illegal oil bunkering is now a booming business in the Niger Delta. It is believed to involve the different local militant groups in creeks, commodity traders, military personnel, international businessmen, and some indigenous oil servicing companies. The successes of illegal oil bunkering in Nigeria have been ascribed to both local and national interest as a result of the profits from this illegal oil business. This study critically examines the key actors of illegal oil bunkering; the root causes and consequences of illegal oil bunkering, and the solutions to the identified challenges.